2022
DOI: 10.1021/acs.jpcc.2c03088
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Diffusion of Cu2+ Ions into Natural Plagioclase Crystals: The Role of Li2O

Abstract: Plagioclase crystals are earth-abundant and low-cost aluminosilicate materials with a high diffusivity of Cu at high temperatures over 1050 °C. The exploration of copper (Cu 2+ )doped plagioclase crystals is hindered by the thermodynamic instability of Cu 2+ at high temperatures over 1050 °C. In this paper, we developed the high-temperature copper−lithium diffusion method for the preparation of blue−green plagioclase crystals doped with Cu 2+ ions. By combining quantitative element distribution characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Natural red and greenish sunstone were obtained from Oregon, USA. Zhou et al [44][45][46] found that copper-diffused plagioclase crystals exhibited red, light red, and blue-green colors under different conditions. Cu diffusion in both red and light red sunstones results in orange fluorescence when illuminated by ultraviolet light at 320 nm, while the Cu-Li diffusion-treated blue-green plagioclase crystal only exhibits weak fluorescence similar to natural sunstone [45,46].…”
Section: Oregon Sunstone Vs Copper-diffused Plagioclase Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural red and greenish sunstone were obtained from Oregon, USA. Zhou et al [44][45][46] found that copper-diffused plagioclase crystals exhibited red, light red, and blue-green colors under different conditions. Cu diffusion in both red and light red sunstones results in orange fluorescence when illuminated by ultraviolet light at 320 nm, while the Cu-Li diffusion-treated blue-green plagioclase crystal only exhibits weak fluorescence similar to natural sunstone [45,46].…”
Section: Oregon Sunstone Vs Copper-diffused Plagioclase Crystalsmentioning
confidence: 99%
“…Zhou et al [44][45][46] found that copper-diffused plagioclase crystals exhibited red, light red, and blue-green colors under different conditions. Cu diffusion in both red and light red sunstones results in orange fluorescence when illuminated by ultraviolet light at 320 nm, while the Cu-Li diffusion-treated blue-green plagioclase crystal only exhibits weak fluorescence similar to natural sunstone [45,46]. Compared with natural Oregon sunstone, which only has a weak emission at ~395 nm, the Cu-diffused sunstone with orange fluorescence has a stronger emission band at ~394 nm and an additional emission band at ~555 nm (Figure 10).…”
Section: Oregon Sunstone Vs Copper-diffused Plagioclase Crystalsmentioning
confidence: 99%